Penalty shoot-outs are tough, but the alternating order is fair. - Silvan Vollmer; David Schoch; Ulrik Brandes (PLoS ONE)
We compare conversion rates of association football (soccer) penalties during regulation or extra time with those during shoot-outs. Our data consists of roughly 50,000 penalties from the eleven most recent seasons in European men's football competitions. About one third of the penalties are from more than 1,500 penalty shoot-outs. We find that shoot-out conversion rates are significantly lower, even for regular penalty takers, and attribute this to worse performance of shooters rather than better performance of goalkeepers. We also find that, statistically, there is no advantage for either team in the usual alternating shooting order. Complemented by a number of detailed observations, these main findings underline that penalty shoot-outs represent a different condition requiring dedicated means of training and coaching.